1986
DOI: 10.1099/00221287-132-8-2367
|View full text |Cite
|
Sign up to set email alerts
|

Dimorphism-associated Variations in the Lipid Composition of Candida albicans

Abstract: Yeast and mycelial forms of Candida albicans ATCC 10231, growing together in 12 h and in 96 h cultures, were separated and their lipids were extracted and characterized. The total lipid content of the yeast forms was always lower than that of the mycelial forms. In 12 h cultures the lipids from the two morphological forms consisted mainly of polar compounds, viz, phospholipids and glycolipids. In 96 h cultures both the yeast and mycelial forms accumulated substantial amounts of apolar compounds, mainly steryl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 20 publications
4
46
2
Order By: Relevance
“…Therefore, their proposed role in P. brasiliensis dimorphism (Manocha, 1980) is questioned. These results contrast with those found in C. albicans whose M form contains significantly higher levels of PC, PS and PI, and lower levels of PE, compared to the Y form (Goyal & Khuller, 1994 (Ghannoum et al, 1986;Mishra et al, 1992;Goyal & Khuller, 1994), the ratio of unsaturated to saturated fatty acids (UFA/SFA) was higher in the M form of P. brasiliensis ( Table 2). The higher levels of SFA in the Y form are probably required to maintain normal basic permeability properties of the plasma membranes at its relatively high growth temperature (Goyal & Khuller, 1994).…”
Section: Resultscontrasting
confidence: 54%
“…Therefore, their proposed role in P. brasiliensis dimorphism (Manocha, 1980) is questioned. These results contrast with those found in C. albicans whose M form contains significantly higher levels of PC, PS and PI, and lower levels of PE, compared to the Y form (Goyal & Khuller, 1994 (Ghannoum et al, 1986;Mishra et al, 1992;Goyal & Khuller, 1994), the ratio of unsaturated to saturated fatty acids (UFA/SFA) was higher in the M form of P. brasiliensis ( Table 2). The higher levels of SFA in the Y form are probably required to maintain normal basic permeability properties of the plasma membranes at its relatively high growth temperature (Goyal & Khuller, 1994).…”
Section: Resultscontrasting
confidence: 54%
“…Lipid analyses of other yeasts and fungi showed that some of them contain significantly larger amounts of sterol glycosides than Saccharomyces and that an increase in its synthesis was induced under stress conditions. 6 In this context, it should be mentioned that insertional mutagenesis experiments with the rice blast fungus Magnaporthe grisea and a subsequent screening procedure revealed mutants with reduced pathogenicity (74). One of these mutants identifies the gene PTH8 (GenBank TM accession number AF027983), the partial sequence of which shows striking similarity to the sterol glucosyltransferases from yeasts.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to S. cerevisiae, significant amounts of SG were occasionally found in other fungi such as C. bogoriensis (4) and Phytium sylvaticum (5), whereas sterol mannosides were detected in the human pathogen Candida albicans (6,7).…”
mentioning
confidence: 93%
“…However, the pathogenic roles of morphological changes remain to be elucidated, because both morphological forms are found in infected tissues and because the molecular mechanisms of the dimorphic transition have not yet been understood clearly. Interestingly, the level of UFAs tended to be higher in the mycelial form than in the yeast form (Sadamori, 1987;Yano et al, 1982;Ghannoum et al, 1986). There is immense interest in studying lipid pathways for several reasons: there are a limited number of effective and safe systemic antifungal drugs, lipids play an important role in pathogenicity and morphogenesis, and lipids provide potential targets for a novel class of antifungals.…”
Section: Introductionmentioning
confidence: 99%